2016
DOI: 10.1142/s2010135x16500272
|View full text |Cite
|
Sign up to set email alerts
|

B-site substituted solid solutions on the base of sodium-bismuth titanate

Abstract: The paper presents results of studies of the formation of phases during the solid-state synthesis in the [(Na 0:5 Bi 0:5 Þ 0:80 Ba 0:20 ðTi 1Ày B y ÞO 3 system of solid solutions with B-site substitutions. The substitutions by zirconium, tin and ion complexes (In 0:5 Nb 0:5 Þ and (Fe 0:5 Nb 0:5 Þ have been studied. It has been found that the synthesis is a multi-step process associated with the formation of a number of intermediate phases (depending on the compositions and calcination temperatures). Single-pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The main drawbacks of BNT for practical applications are its large coercive field and high electrical conductivity. Several studies have been reported in the literature on the modifications of the composition of BNT to overcome the drawbacks and to improve its piezoelectric properties 5–10 . Most of these studies are centered on the substitution of Na + by K + in Bi 0.5 (Na 1‐ x K x ) 0.5 TiO 3 , and these compositions are considered as potential candidates for various piezoelectric applications 11–23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main drawbacks of BNT for practical applications are its large coercive field and high electrical conductivity. Several studies have been reported in the literature on the modifications of the composition of BNT to overcome the drawbacks and to improve its piezoelectric properties 5–10 . Most of these studies are centered on the substitution of Na + by K + in Bi 0.5 (Na 1‐ x K x ) 0.5 TiO 3 , and these compositions are considered as potential candidates for various piezoelectric applications 11–23 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been reported in the literature on the modifications of the composition of BNT to overcome the drawbacks and to improve its piezoelectric properties. [5][6][7][8][9][10] Most of these studies are centered on the substitution of Na + by K + in Bi 0.5 (Na 1x K x ) 0.5 TiO 3 , and these compositions are considered as potential candidates for various piezoelectric applications. [11][12][13][14][15][16][17][18][19][20][21][22][23] Sasaki et al studied the structural, dielectric, and piezoelectric properties of Bi 0.5 (Na 1-x K x ) 0.5 TiO 3 solid solution series and found the morphotropic phase boundary (MPB) region in the range x = 0.16-0.20 and the piezoelectric properties are maximum in this compositional range.…”
mentioning
confidence: 99%
“…The main drawbacks of BNT for practical applications are its large coercive eld and high electrical conductivity. Several studies have been reported in the literature on the modi cations of BNT to overcome these drawbacks and to improve its piezoelectric properties [5][6][7][8][9][10]. Most of these studies are centered on the substitution of Bi-or Na-site of the perovskite lattice by other metal ions of comparable size, ionic character, etc.…”
Section: Introductionmentioning
confidence: 99%